ANALISIS SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SEPEDA MOTOR HONDA MEREK VARIO PADA PD. DAYA MOTOR SUNGAI BAHAR MUARO JAMBI - Ahmad Tarmizi (Universitas Batanghari Jambi, 2017)
The purpose of the research is to find out and analyze the attitude of consumers towards products of honda motor vehicles branded vario on PD. Motor Power Muaro Jambi. The number of samples that will be taken is as much as 100 people respondents. Sample withdrawal technique is done in a non probability of simple random sampling. Analysis tools are used multiple linear regression. Research results from theTest F F values obtained to calculate probability with 41.855 of 0.000. Because F count 42.193 > F 2.47 and the probability Table is much smaller than 0.05 regression models then can be used to predict future purchasing decisions (the dependent variable) or it can be said that all independent variables namely Utilitarian Function, the expression value, maintain the ego and knowledge together effect on the dependentvariable consumer purchasing decisions against the Honda brand Vario. The coefficient of determination (R2) above shows the magnitude of the adjusted R2 is 0.640, this means that 64% of the variations in purchase decisions can be explained by the variation of 4 independent variables. The t-test analysis results above is a value t calculate on variable Utilitarian (X 1). variable expression of the value (X 2) Defending the Ego (X 3), variable knowledge (X 4) significance level of 0.000 significance probability α = < 0.05, then Ho denied and Ha is received. This means the variables x 1, x 2,x 3, X 4 positive and significant effect against the decisionKey word: attitude, consumer, purchase